P-65 The physician response unit, supporting palliative and end of life patients in the community. (20th March 2022) - Jassal, Radhika; Harris, Amy; Hannaford, Katy; Whitburn, Tara; Joy, Tony
Abstract : Background: The Physician Response Unit (PRU) is a Community Emergency Medicine model, bringing highly skilled medical care to the patient. This is in the form of a senior Emergency Physician and an ambulance service clinician equipped with point-of-care diagnostics, medications and they can access health records including Coordinate My Care. Aim: To show the activity and interventions carried out by the PRU in patients who have been identified as having palliative care needs or being at the end of life. Method: A retrospective descriptive analysis of patients identified by the PRU as having palliative care needs or being at the end of life at the point of review between January 2021 to April 2021. Information recorded included origin of the call, outcome of the visit and whether they were known to palliative care services prior to the review. Results: A total of 58 palliative care patients were seen by the PRU in their own home between January and April 2021. 56 patients following review by the PRU stayed at home. 32 of the calls requesting a PRU visit originated from an ambulance crew that was already at the place of residence. Of the patients in the study, 22 were known to palliative care services prior to the review, and 34 were not known with their services previously. The most common reasons for review included possible end of life care for 19, followed by difficulty in breathing in 10. Conclusion: In this study the majority of patients reviewed by the PRU managed to stay at home despite an ambulance being called. Over half the patients who were identified with palliative or end of life care needs were not known to palliative care services prior to this emergency review.